Elevating Clinical Informatics: Dynamic Resident Training to Enhance Subspecialty Appeal - Mrosak, Justine; Jelinek, Ryan; Pandita, Deepti (Applied Clinical Informatics, 2025)
Objective This study aimed to bridge the educational gap in clinical informatics (CI) at the residency level and stimulate interest in CI as a rewarding career path.Methods We developed an innovative CI and quality improvement (QI) resident rotation. This rotation replaced traditional QI blocks for Internal Medicine and several other residency programs, offering comprehensive exposure to core informatics and QI principles. The curriculum featured prerecorded didactics, hands-on projects, department meetings, and an optional EPIC SmartUser program. Resident participation and feedback were evaluated through postrotation surveys.Results Since its inception on July 1, 2022, 57 residents have completed the rotation, with a majority rating their experience favorably. Residents also valued the educational course content and expressed an increased likelihood of integrating informatics into their future careers.Conclusion The rotation has successfully integrated into existing multiple residency programs, demonstrating an effective model for delivering informatics education. Initial outcomes show enhanced resident engagement and competency in CI, promising a progressive impact on the future physician workforce. Continued expansion and evaluation of this rotation are expected to further encourage formal CI training and career interest.
Keywords: medical education; medical informatics; quality improvement; informatics training